Plasmodium falciparum Histone Acetyltransferase, a Yeast GCN5 Homologue Involved in Chromatin Remodeling - Fan, Qi (American Society for Microbiology, 2004)
The yeast transcriptional coactivator GCN5 (yGCN5), a histone acetyltransferase (HAT), is part of large multimeric complexes that are required for chromatin remodeling and transcriptional activation. Like other eukaryotes, the malaria parasite DNA is organized into nucleosomes and the genome encodes components of chromatin-remodeling complexes. Here we show that GCN5 is conserved in Plasmodium species and that the most homologous regions are within the HAT domain and the bromodomain. The Plasmodium falciparum GCN5 homologue (PfGCN5) is spliced with three introns, encoding a protein of 1,464 residues. Mapping of the ends of the PfGCN5 transcript suggests that the mRNA is 5.2 to 5.4 kb, consistent with the result from Northern analysis. Using free core histones, we determined that recombinant PfGCN5 proteins have conserved HAT activity with a substrate preference for histone H3. Using substrate-specific antibodies, we determined that both Lys-8 and -14 of H3 were acetylated by the recombinant PfGCN5. In eukaryotes, GCN5 homologues interact with yeast ADA2 homologues and form large multiprotein HAT complexes. We have identified an ADA2 homologue in P. falciparum, PfADA2. Yeast two-hybrid and in vitro binding assays verified the interactions between PfGCN5 and PfADA2, suggesting that they may be associated with each other in vivo. The conserved function of the HAT domain in PfGCN5 was further illustrated with yeast complementation experiments, which showed that the PfGCN5 region corresponding to the full-length yGCN5 could partially complement the yGCN5 deletion mutation. Furthermore, a chimera comprising the PfGCN5 HAT domain fused to the remainder of yeast GCN5 (yGCN5) fully rescued the yGCN5 deletion mutant. These data demonstrate that PfGCN5 is an authentic GCN5 family member and may exist in chromatin-remodeling complexes to regulate gene expression in P. falciparum.